Carbon Domains on MoS2/TiO2 System via Catalytic Acetylene Oligomerization: Synthesis, Structure, and Surface Properties - Cravanzola, Sara; Cesano, Federico; Gaziano, Fulvio; Scarano, Domenica (Frontiers in Chemistry, 2017)
Carbon domains have been obtained at the surface of a MoS2/TiO2 (Evonik, P25) system via oligomerization and cyclotrimerization reactions involved in the interaction of the photoactive material with acetylene. Firstly, MoS2 nanosheets have been synthesized at the surface of TiO2, via sulfidation of a molybdenum oxide precursor with H2S (bottom-up method). Secondly, the morphology and the structure, the optical and the vibrational properties of the obtained materials, for each step of the synthesis procedure, have been investigated by microscopy and spectroscopy methods. In particular, transmission electron microscopy images provide a simple tool to highlight the effectiveness of the sulﬁdation process, thus showing 1L, 2L, and stacked MoS2 nanosheets anchored to the surface of TiO2 nanoparticles. Lastly, in-situ FTIR spectroscopy investigation gives insights into the nature of the oligomerized species, showing that the formation of both polyenic and aromatic systems can be taken into account, being their formation promoted by both Ti and Mo catalytic sites. This finding gives an opportunity for the assembly of extended polyenic, polyaromatic or mixed domains firmly attached at the surface of photoactive materials. The presented approach, somehow different from the carbon adding or doping processes of TiO2, is of potential interest for the advanced green chemistry and energy conversion/transport applications.